Phosphorous Fractions in Weathered Tropical Soils After Application of Conventional and Alternative P Fertilizers - da Silva Sandim, Aline [UNESP]; da Silva, Lucas Jónatan Rodrigues [UNESP]; Deus, Angélica Cristina Fernandes [UNESP]; Penn, Chad; Büll, Leonardo Theodoro [UNESP] (My University, 2023)
Purpose: Phosphorus (P) is a limiting nutrient for agriculture globally. This study aims to investigate the potential of alternative P sources to improve P efficiency in weathered tropical soils of the Brazilian Cerrado region. Methods: We evaluated P fractions in two soil types a tropical Ferralsol and an Arenosol, both with different maximum adsorption capacities of phosphorus, fertilized with various phosphate sources. The experiment followed a randomized block design, using a factorial scheme of 2 × 4 for each soil, with and without limestone correction, and four fertilizer types: two precipitated phosphorus sources, reactive phosphate rock, triple superphosphate, and a control group. The study was conducted under laboratory conditions, and we assessed soil and fertilizer chemical properties and phosphorus fractions and diffusion. Results: Our findings indicate that precipitated phosphorus exhibited similar or better behavior in terms of availability and diffusion than triple superphosphate, despite its lower water solubility. After lime application, we observed an increase in moderately labile P fractions in the soil where precipitated phosphorus source was applied. Furthermore, we found that soil chemical properties (soil pH, soil organic matter, cation exchange capacity, and potential acidity) influence P fractions in weathering tropical soils. Conclusion: The results suggest that Precipitated phosphorus source is a promising alternative P source that could potentially improve P efficiency in weathered tropical soils. Our findings highlight the need to consider soil chemical properties in the P dynamics of these soils.
Keywords: Alternative phosphorous sources; Phosphorous availability; Phosphorous diffusion; Phosphorus efficiency use